2013
DOI: 10.3349/ymj.2013.54.4.949
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Wall Thickening Is Associated with the Granulation Tissue Formation Around Silicone Stents in Patients with Post-Tuberculosis Tracheal Stenosis

Abstract: PurposeTracheal restenosis due to excessive granulation tissue around a silicone stent requires repeated bronchoscopic interventions in patients with post-tuberculosis tracheal stenosis (PTTS). The current study was conducted to identify the risk factors for granulation tissue formation after silicone stenting in PTTS patients.Materials and MethodsA retrospective study was conducted between January 1998 and December 2010. Forty-two PTTS patients with silicone stenting were selected. Clinical and radiological v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The main cause of restenosis, post-stenting, is tracheal wall thickening due to granuloma formation 23,24 . Our initial hypothesis was that a paclitaxel DES would improve the results since epithelial reaction would be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of restenosis, post-stenting, is tracheal wall thickening due to granuloma formation 23,24 . Our initial hypothesis was that a paclitaxel DES would improve the results since epithelial reaction would be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of interventional bronchoscopic techniques have recently been used to treat airway stenosis. This approach produced some beneficial effects, but airway restenosis occurred in some of the patients [1,2,3,9,10,11,13,14]. Reported data show a rate of restenosis from 40 to 70% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this kind of intervention tends to entail recurrent stenosis due to granulation tissue formation. The repeated procedures required [1,2,3,9,10,11,13,14] make airway stenosis a clinical challenge. Therefore, exploring new treatments is important for better clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that keloid formation is associated with different genetic and epigenetic factors, which is highlighted by the fact that keloid formation is more common in individuals with a nonwhite ethnicity and a positive family history of keloid formation [42]. EOM et al [43] identified tracheal wall thickness as an independent predictor for granulation tissue formation after airway stenting in patients suffering from post-tuberculosis tracheal stenosis. This might be explained by inter-individual differences in healing responses.…”
Section: Genetic Susceptibilitymentioning
confidence: 99%